2017
DOI: 10.1088/1475-7516/2017/11/005
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic viscosity as a remedy for tension between PLANCK and LSS data

Abstract: Measurements of σ 8 from large scale structure observations show a discordance with the extrapolated σ 8 from Planck CMB parameters using ΛCDM cosmology. Similar discordance is found in the value of H 0 and Ω m . In this paper, we show that the presence of viscosity, shear or bulk or combination of both, can remove the above mentioned conflicts simultaneously. This indicates that the data from Planck CMB observation and different LSS observations prefer small but non-zero amount of viscosity in cold dark matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 94 publications
0
55
0
Order By: Relevance
“…Let us also mention at this point that there are a few alternative approaches attempting to cure the σ8-tension, e.g. using possible effects of viscosity of the cosmic fluid (Anand et al 2017), or some phenomenological interactions between DM and DE (Barros et al 2018;An, Feng & Wang 2017;Wang et al 2016), or even using a small amount of spatial curvature (Ooba, Ratra & Sugiyama 2017 In fact, dynamical dark energy models may exhibit degeneracies with the cosmic neutrino background since massive neutrinos can suppress the power spectrum (and hence the structure formation) on small scales (see Hu, Eisenstein & Tegmark 1998;Shoji & Komatsu 2010). However, the above mentioned papers show that the effect proves insufficient to relax the σ8-tension, if the allowed neutrino mass hierarchies are to be respected.…”
Section: Analytical Calculation Of ∆ F σ 8 (Z) In the Rvm: Solving Thmentioning
confidence: 99%
“…Let us also mention at this point that there are a few alternative approaches attempting to cure the σ8-tension, e.g. using possible effects of viscosity of the cosmic fluid (Anand et al 2017), or some phenomenological interactions between DM and DE (Barros et al 2018;An, Feng & Wang 2017;Wang et al 2016), or even using a small amount of spatial curvature (Ooba, Ratra & Sugiyama 2017 In fact, dynamical dark energy models may exhibit degeneracies with the cosmic neutrino background since massive neutrinos can suppress the power spectrum (and hence the structure formation) on small scales (see Hu, Eisenstein & Tegmark 1998;Shoji & Komatsu 2010). However, the above mentioned papers show that the effect proves insufficient to relax the σ8-tension, if the allowed neutrino mass hierarchies are to be respected.…”
Section: Analytical Calculation Of ∆ F σ 8 (Z) In the Rvm: Solving Thmentioning
confidence: 99%
“…In these analyses the base model is normally the ΛCDM cosmology. Although there are many tensions like σ 8 [58][59][60] or H 0 tension [61] among different cosmological measurements under ΛCDM framework still it is undeniable that ΛCDM is the best model available so far to fit the CMB data. The need to accommodate sterile neutrinos, motivated by SBL neutrino oscillation experiments, requires one to introduce large self interaction in the sterile neutrino sector.…”
Section: Discussionmentioning
confidence: 99%
“…The perturbed part of continuity equation for the cold dark matter, T µν ;µ = 0, provides us two basis sets of equations, known as density perturbation equations and velocity perturbation equations [17].…”
Section: )mentioning
confidence: 99%
“…Massive sterile neutrino in the system was reported to reduce the tension in σ 8 -Ω 0 m plane but it fails to do that in H 0 − Ω 0 m [8,15]. Interestingly, in ref [17] it has been shown that viscosities in CDM on large scales solves both σ 8 and H 0 tension simultaneously. We, therefore, use the viscous dark matter description to the study of neutrinos.…”
Section: Introductionmentioning
confidence: 99%